The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1007/s10646-016-1632-z
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics of selenium in the slider turtle, Trachemys scripta

Abstract: Selenium (Se) is an essential element that can be harmful for wildlife. However, its toxicity in poikilothermic amniotes, including turtles, remains poorly investigated. The present study aims at identifying selenium toxicokinetics and toxicity in juvenile slider turtles (age: 7 months), Trachemys scripta, dietary exposed to selenium, as selenomethionine SeMet, for eight weeks. Nondestructive tissues (i.e. carapace, scutes, skin and blood) were further tested for their suitability to predict selenium levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Some authors like Ley-Quiñonez et al (2011) mention the difficulty in establishing whether the high concentrations of Se in sea turtles can be considered a toxic factor; however, selenomethionine is considered to be the primary form of organic selenium relevant for bio-accumulation and toxicity in wildlife (Dyc et al, 2015(Dyc et al, , 2016. It has been suggested that the presence of Se in sea turtle eggs could be toxic for the embryo (Lam et al, 2006), and a mother-embryo metal transfer has been demonstrated in sea turtles (Paez-Osuna et al, 2010a,b, 2011; Dyc et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors like Ley-Quiñonez et al (2011) mention the difficulty in establishing whether the high concentrations of Se in sea turtles can be considered a toxic factor; however, selenomethionine is considered to be the primary form of organic selenium relevant for bio-accumulation and toxicity in wildlife (Dyc et al, 2015(Dyc et al, , 2016. It has been suggested that the presence of Se in sea turtle eggs could be toxic for the embryo (Lam et al, 2006), and a mother-embryo metal transfer has been demonstrated in sea turtles (Paez-Osuna et al, 2010a,b, 2011; Dyc et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, species-specific toxicokinetic processes (absorption, distribution, metabolism, and elimination), which are poorly understood for reptiles in general, govern the trace element differences among various tissues. Only a few descriptions of these processes exist for freshwater turtle species, and even then only for Cd, Se, and Hg (Blanvillain et al, 2007;Dyc et al, 2016;Guirlet and Das, 2012;Schwenter, 2007). Since internal tissue concentrations reflect the integration of all trace element exposure pathways, they are more informative as biomonitoring matrices than external ones (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The keratinized scutes surround and protect the carapace in chelonids. It has been suggested that keratin is more indicative of long-term toxic element exposure and represents a non-lethal sampling method for determining total body toxic element burden (Sakai et al, 2000;Day et al, 2005;van de Merwe, 2008;Komoroske et al, 2011;Dyc et al, 2016). In turtles from this study, we found that arsenic and selenium were higher in blood compared to keratin, suggesting a more recent exposure to these elements, while mercury was lower in the blood compared to keratin, indicative of a more historal exposure to this element.…”
Section: Blood and Keratin Toxic Element Correlationsmentioning
confidence: 45%
“…Leatherbacks have been shown to have the highest selenium concentrations in blood for reasons that remain unknown, but this has been attributed to their diet (Innis et al, 2010) and high daily food intake (Heaslip et al, 2012;Perrault, 2014). It is likely that blood selenium concentrations are accurate predictors of diet, as turtle toxicokinetic studies have observed increasing blood selenium concentrations with an increase in selenium dosage (Dyc et al, 2016). This suggests that loggerheads are less exposed to dietary selenium than leatherbacks, but have a greater intake than green turtles due to diet and volume of food intake.…”
Section: Blood and Keratin Toxic Element Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation